Ultrastructure of royal palm (Roystonea regia) leaf sheath - ULFA ADZKIA; NARESWORO NUGROHO; ISKANDAR Z. SIREGAR; Lina Karlinasari (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Adzkia U, Nugroho N, Siregar IZ, Karlinasari L. 2020. Ultrastructure of royal palm (Roystonea regia) leaf sheath. Biodiversitas 21: 967-974. The royal palm (Roystonea regia (Kunth) F.Cook is one of the palm species that are many planted along the streets as part of urban landscapes. As biologically products, in nature they can self-cleaning with drop off their big leaves. The study aims to examine the morphological characteristics of ultrastructure and elemental content, crystallinity, as well as fibers derivation characteristics from the royal palm. The samples were taken out from leaf sheaths that divided into three sections along the width of i.e. outside, middle, and inside; in two conditions of leaf sheaths namely green and brownish-dry. The morphology structure and elemental content were observed by the Scanning Electron Microscopy (SEM) and the Energy Dispersive X-ray analysis (EDX), while the crystallinity was analyzed using X-ray diffraction (XRD), and fiber characteristics were measured to determine cell dimensions as well as to calculate Runkle ratio (RR), muhlsteph ratio (MR), coefficient of rigidity (CR), felting powder (FP), and flexibility ratio (FR). The diameter of palm fiber bundles was decreased from outside towards inside. The model of vascular tissue was rounded which located in the central region of the fiber bundles. The silicon content in the inside section was lower than those in the middle and outside sections. It was in line with the degree of crystallinity in the inside section which that higher than other sections. The highest degree of crystallinity was about 18 %. The fiber length of royal palm leaf sheath was in values around 6000 ?m. However, the royal palm leaf sheath had thick fiber walls and thin lumen, as well as other fiber derivation characteristics of muhlsteph ratio, the coefficient of rigidity and the flexibility ratio, were in low-quality values. For that reason, the study provides information that the royal palm sheath was recommended as a composite reinforcing material.